Charles McCrary, Sincerely Held: American Secularism and Its Believers - Poulos, Elenie (Journal for the Academic Study of Religion, 2022)
Charles McCrary, Sincerely Held: American Secularism and Its Believers. Class 200: New Studies in Religion. Chicago: University of Chicago Press, 2021, pp. 296, ISBN: 9780226817958 (pbk). US30.00.